Penggunaan Metode System Development Life Cycle ( SDLC) dalam Analasis dan Perancangan Sistem Informasi Penerimaan Kas Sekolah - Setiany, Anggit Prastika; Noviyanto, Dian; Irfansyahfalah, Muhammad; Aisah, Siti; Saifudin, Aries; Kusyadi, Irpan (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
Implementation of Accounting Information System in educational institutions like school is important to do. With information system, delivery information accounting at school goes well on reach goals that determined before. School cash receipts with information accounting system should be support with information system for an effective administration process. Purpose of this research is give the solution about information system of school cash receipts to handle the problem in the system that has been applied. A plan with MYSQL and PHP application system passed through by DBMS (Database Management System),used for creating the management with accounting information system. With SDLC (System Development Life Cycle) method does for program school accounting of information system. Before used SDLC method,school used manual system that cause much trouble, one of them is data dissonance existence with cash receipts evidence. After the implementation of the SDLC method and a complete DBMS design can make it easier for programmers to implement into programming languages, can reduce errors and speed up work.